MSME Development Strategy Of Mendoan And Tempe Keripik ECO 21 Sawangan Puwokerto With SWOT Analysis - Kholilur Rahman; Salmaa Aliifah Kultsum (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2022)
Micro, Small, and Medium Enterprises (MSMEs) must never be separated from the various problems that exist, both internal and external problems, as well as those experienced by the Mendoan and Tempe Keripik Industry ECO 21 Sawangan Purwokerto, starting from the internal problems that occurred within the company, namely the decline in sales of mendoan and tempe keripik which have an impact on annual income, and external problems, namely the lack of consumer buying interest in traditional foods. This study aims to formulate a strategy for developing micro, small and medium enterprises (MSMEs) for mendoan and tempe keripik ECO 21 Sawangan, Purwokerto, using SWOT analysis. This research uses a qualitative descriptive approach, collecting data through observation, interviews, and documentation. The SWOT analysis technique aims to identify various factors systematically and formulate a company's strategy. The results of this study indicate that the development strategy of the Mendoan and Tempe Keripik Industry ECO 21 Sawangan, Purwokerto that the company can use, namely, the SO ( strength-opportunity ) strategy whose purpose is to improve product quality, follow government counseling, and utilize internet technology such as social media. To increase profits. The WO ( weakness-opportunity ) strategy aims to initiate product innovation, promote and use the profits to buy modern production equipment; the ST strategy ( strength-threats ) aims to establish good relationships with consumers and maintain product quality in order to gain loyalty from consumers, while the WT ( weakness-threats ) strategy aims to innovate on existing products and use internet media to analyze the market.